أفكار علماء الكلام من المعتزلة تأثير فلسفة أفلاطون في - Mohd Radhi Ibrahim (Universiti Sains Islam Malaysia, 2024)
This study is an attempt to examine the influence of Plato philosophy in 'ilm al-kalam. This study also indicates the influence of Greek philosophy in 'ilm al-kalam. To achieve our objective, I will briefly examine the Mutakallimun's views on ontology and epistemology. This study indicates that Abu al-Hudhayl's knowledge of Greek theory of existence contributes to his significant theory on the attributes of God. In epistemology we observe the influence of Plato b philosophy on Abu 'Ali b definition o f knowledge.